Using Technology to Improve Education for Marginalised Girls: Lessons in implementation from the Girls’ Education Challenge - Anonymised for Peer Review Purposes (EdTech Hub, 2023)
This article presents the findings of an in-depth study on the implementation of six EdTech-supported projects within the UK Government Foreign, Commonwealth and Development Office (FCDO)’s Girls’ Education Challenge portfolio, which aims to improve education for the world’s most marginalised girls. Using primary key informant interviews and secondary data from sampled projects, the study identifies the core components related to the implementation of EdTech within the sampled projects: evidence-informed design and delivery; building and maintaining relationships across and between stakeholders; comprehensive and continuous training and capacity development; and situating EdTech within a broader holistic model that prioritises gender inclusion to optimise implementation for marginalised girls. In doing so, the study provides key lessons for optimising the future implementation of EdTech for marginalised girls. Keywords: educational technology; girls’ education; programme implementation; Covid-19 An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8116387 ZenodoArchiveConcept: 8116386 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8116387 10.53832/edtechhub.0172 2339240:V4SEB3GI 2405685:V8CZHW5B 2405685:ZY6RMGAF
Keywords: _r:AddedByZotZen

The relationship between educational television and mathematics capability in Tanzania - Watson, Joseph; Hennessy, Sara; Vignoles, Anna (British Journal of Educational Technology, 2020)
Previous studies have frequently demonstrated that educational television viewing can have a positive effect on learning in low-income country contexts when shows are delivered in controlled settings. However, the consequence of day-to-day viewing in such contexts has scarcely been considered. Additionally, no recent published research has provided any information on the costs of educational television. The lack of research in these areas is striking. Examining educational television viewing in monitored settings provides limited information on the influence of routine television consumption. Further, the broad reach of numerous educational television programmes should provide low perviewer costs and, resultantly, strong cost-effectiveness findings. This PhD study therefore examined (1) the association between educational television exposure and mathematics capability and (2) the cost effectiveness of educational television interventions. To achieve this, research was carried out that centred on Ubongo Kids – a popular Tanzanian-produced show delivering mathematics-focused content.
KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.13047 10.17863/cam.54714 2339240:6LGJJU8F 2339240:MVL3KA6H 2339240:U3SHRB68 2339240:XZDCXAZ7 2405685:8WKWEBZZ 2405685:A5XKUF3W 2405685:CHDUKI36 2405685:VJ8U5IDE 2405685:YENK6ASB
Keywords: Tanzania; ___working_potential_duplicate; cost effectiveness; educational television; mathematics; ⛔ No DOI found